Sistem Pakar Diagnosa Penyakit Tanaman Kopi Menggunakan Metode Dempster Shafer - Boby Riansyah; Didik Kurniawan; Made Same (Jurnal Komputasi, 2021)
At present the total area of Indonesian coffee plantations is ranked second in the world, but for the production and export of Indonesian coffee there is at number four in the world. The low productivity of coffee is caused by inadequate crop cultivation techniques, this encouraging various plant growth disorders. Based on the problems, coffee farmers need a tool that can provide information about coffee plants and diseases that attack coffee plants and provide solutions to handle these diseases. One branch of computer science that can help is the expert system (Expert System). Expert systems use the knowledge of an expert which is intended to increase knowledge into computers. This research used Dempster-Shafer method to diagnose and to knowing the degree of accuracy of the diagnoses results. Information system and expert system of coffee plants diagnose contains information about plants management that begins from planting until harvest. This system built based on the web, with this system is expected to help provide solutions to handle the coffee plants that have disease, that many coffee plants can be saved from disease and can increase the productivity of coffee plants.